Investigation of detection wavelength of Quantum Well Infrared-Photodetector - Sung Ho Hwang; Jae Gu Lim; Jin Dong Song; Jae Cheol Shin; Du Chang Heo; 최원준 (한국진공학회, 2015)
We report on GaAs/AlGaAs quantum well infrared photodetectors (QWIPs) that can cover the spectral range of 3.6-25 μm. One advantage of the GaAs QWIPs is the wavelength tenability as a function of their structural parameters. We have performed a systematic calculation on the detection wavelength of a typical GaAs/AlxGa1-xAs multi-quantum-well photodetector, with the aluminum mole fraction (x) of AlxGa1-xAs barrier in the range of 0.15- 0.43 and the quantum-well width range from 30 to 60 ？. Design and fabrication of a QWIP based on GaAs/Al0.23Ga0.77As structure with 37 ？-thick well width has been carried out. The calculated operation wavelength of the QWIP is in a good agreement with the experimental data taken by photo response and activation energy calculation from thermal quenching of integrated photoluminescence.